An Evaluation of the Precision of Ocular Trauma Score and Factors for Poor Visual Outcomes in Open Globe Injury: A Retrospective Analysis of Resourcelimited Hospital Settings - Oughtkaew, Takarn; Puangrab, Siwatus (Siriraj Medical Journal, 2024)
Objective: To evaluate the accuracy and validity of ocular trauma scores (OTS) among patients with open globe injury (OGI) in rural hospital settings and to identify the determinants predicting poor visual outcomes. Materials and Methods: A single-center retrospective cohort study was conducted through a chart review of OGI patients between July 2018 and June 2023 at Bueng Kan Hospital. Demographic and preoperative factors affecting the final visual outcome were evaluated. OTS score for each patient was calculated and categorized. Final VA after 6 months was compared to the predicted VA from OTS study. Poor visual outcome was defined as legal blindness after 6 months of treatment. Results: Thirty-nine eyes from patients with a mean age of 44.05 years were evaluated. Most subjects were male (94.87%), and workplace injuries were the most common (78.38%). Compared to the OTS study, patients in OTS category 2 achieved a significantly higher percentage of better final VA, while categories 3 and 4 showed similar outcomes. OTS category 1 patients had a lower proportion of no light perception (NLP) outcomes, though the difference was not significant. Poor visual outcomes were predicted by initial VA (OR=4.64), wound extension ≥10 mm (OR=20.66), and lens injury (OR=7.44). Conclusion: OTS is beneficial for predicting final vision in patients with OGI, particularly with less severe trauma. Severe cases often lead to better visual outcomes, emphasizing the need for cautious management and counseling by ophthalmologists. Factors that estimate poor visual outcomes involve poor initial VA, wound extension  10 mm, and lens damage.